Catalytic Conversion of Starch to 5-Hydroxymethylfurfural by Tin Phosphotungstate - Hao, Jiawen; Song, Xueping; Jia, Shaowu; Mao, Wei; Yan, Yuxiao; Zhou, Jinghong (Frontiers in Energy Research, 2021)
Heteropoly acids containing Brønsted and Lewis acids show excellent catalytic activity. Brønsted acids promote the depolymerization of polysaccharides (such as starch and cellulose) into glucose, while Lewis acids catalyze the conversion of glucose to 5-hydroxymethylfurfural (HMF). Designing stable Brønsted-Lewis acid-containing bifunctional heterogeneous catalysts is crucial for the efficient catalytic conversion of polysaccharides to HMF. In this study, a series of Brønsted -Lewis acid bifunctional catalysts (SnxPW, X = 0.10-0.75) were investigated for the conversion of cassava starch to HMF. The structure of the catalysts was characterized by X-ray diffraction, Fourier transform infrared spectroscopy, Pyridine Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The acid strength and acid capacity were also investigated. The effects of reaction time, temperature, catalyst concentration, and cassava starch concentration on the selectivity, conversion rate, and yield were examined. The results showed that, among the analyzed catalysts, Sn0.1PW presented the best ability under the test conditions for catalyzing the conversion of starch to HMF. At the optimized conditions of a reaction temperature of 160 °C, a catalyst dosage of 0.50 mmol/gstarch, and a 1h reaction time, the starch conversion rate was 90.61%, and the selectivity and yield of HMF were 59.77% and 54.12%, respectively. Our findings contribute to the development of HMF production by the dehydration of carbohydrates.